Inside the American couple : new thinking/new challenges - Yalom, Marilyn; Carstensen, Laura L. (University of California Press, 2002)
One of the most fundamental human urges is to form a pair. Despite many tendencies that threaten traditional marriage and even make committed cohabitation problematic, very few people live through adulthood without at least one lengthy relationship, and up to ninety percent of Americans marry at least once in their lives.